On the Spirit of Freedom in Hebrew Culture and Its Legal Safeguarding System - SUN Yuchun, LI Guoqiang, CHANG Xiyin; ZHOU Enhui, ZHANG Zhe (Journal of Research for Christianity in China (JRCC), 2025)
The French Declaration of the Rights of Man and of the Citizen, the American Declaration of Independence, and the Emancipation Proclamation stand as epoch-making milestones in modern world history! Yet some may overlook that these great declarations trace their theoretical origins and fundamental spirit back to Hebrew culture—and with remarkable clarity and completeness! Both the Old and New Testaments of the Bible are imbued with a fresh, noble, and comprehensive spirit of freedom, accompanied by a detailed legal framework for its protection! On this foundation, the spirit of freedom became a profound and enduring tradition within Hebrew culture, ultimately providing tremendous momentum for the development of world civilization! This paper attempts to offer some novel insights into the spirit of freedom and the legal protection system within Hebrew culture. The paper is divided into four sections: First, freedom in the face of nature. Second, freedom in the face of social institutions. Third, freedom in the face of sin and transgression. Fourth, a concise summary.